Conventional and Molecular Identification of Candida spp. And Antifungals Susceptibility Test in Pregnant Women - Jabar, Douaa; Aljaza, Diyaa (University of Thi-Qar Journal of Science, 2022)
Candida species are medically significant because they are the most frequent opportunistic mycosis in the worldwide. Because of hormonal and biochemical fluctuations, Fungal infections in the vagina are tenfold during pregnancy. Increased antibiotic usage and the presence of high levels of reproductive hormones during pregnancy both promote Candida species colonization. The study aimed to shed light on the relationship between Urinary tract infection UTI and candidiasis and determines the genetic patterns and their prevalence among women. There are 90 samples of urine and vaginal swabs collected from pregnant women with UTI at ages ranging from (15-40) years. All samples cultured on SDA, MSA and MEA. Several tests were used to identify the types of isolated yeasts, including growth on Chromogenic agar medium, as well as biochemical and molecular tests using primers ITS1, 4. The Results found that a nine species of Candida were isolated on Chromogenic: C. albicans, C. glabrata, C. tropicalis, C. dubliniensis, C. parapsilosis, C. krusei, C. kefyr, C. membranifaciens and C. utilis, Also, showed the number of yeasts that were genetically diagnosed by molecular diagnosis was eight species of yeasts as follows 3 isolates C. albicans from 33% and one isolate for each of the following types C. orthopsilosis, C. glabrata, C. tropicalis, C. dubliniensis and C. parapsilosis with 11% of all isolates where C. albicans showed the highest percentage. The results of the statistical analysis of the isolates showed that the most affected age group of pregnant women was (26-30), (21-25 year).